Influences of sintering temperature on pore morphology, porosity, and mechanical behavior of porous Ti. (19th October 2021) - Yang, Ding; Tian, Zhenyun; Song, Jingjing; Lu, Tengfei; Qiu, Guibao; Kang, Jialong; Zhou, Hanghang; Mao, Hongxia; Xiao, Jian
Abstract: The purpose of this study was to determine the influences of the sintering temperature on the pore morphology, porosity, and mechanical behavior of titanium foams. Porous Ti samples were successfully manufactured using the metal powder metallurgy method in conjunction with sintering at the four temperatures (900, 1000, 1100, and 1200 °C). The sintering temperature significantly influenced the pore morphology, porosity, and mechanical behavior of the titanium foams. The titanium foams were characterized using an optical microscope in conjunction with scanning electron microscopy. A fracture showed the appearance and growth of a sintering neck between adjacent particles. As the sintering temperature increased, the sintering necks gradually became clearer. The porosity decreased from 56.48% to 46.83% as the sintering temperature increased from 900 °C to 1200 °C, while the initial yield strength of the porous titanium increased from 101.81 to 208.01 MPa. The porous titanium foams produced by the metal powder metallurgy method have a significant utilization potential in hard-tissue engineering.